PENEMPATAN DAN ORIENTASI PERSONALIA DALAM PENDIDIKAN ISLAM - Mukhroji Mukhroji (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2012)
Abstract : Placement of human resources is a process of activities implemented by a human resources manager within an organization to determine one’s location and position to do a job. It is similar to placement of human resources or personnels in Islamic education conducted by the Chairperson. Placement may occur to those who occupy a really new job, who get promotion, transfer of duties, and demotion. High-quality human resources are expected to significantly be subject of development in order to be more successful in managing resources for the welfare of society. In order to manage educational organizations effectively and efficiently, personnel management that is able to put human resources in accordance with the qualifications and competence determined by the educational organization is highly required. Keyword: Human Resources, placement, orientation, Islamic education.